2018
DOI: 10.1139/cjz-2017-0058
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and offspring effects on the timing of parturition in western Steller sea lions (Eumetopias jubatus)

Abstract: Identifying factors that affect the timing of parturition among annual breeders is important to aid our understanding of how variations may adversely affect population trends over both short and long temporal scales. We investigated the effect of several parameters on the timing of parturition among individual Steller sea lions (Eumetopias jubatus (Schreber, 1776)) over 6 years between 2005 and 2016 using an information–theoretic approach. In addition to the random effect of year, birth and care of a pup in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…However, sample size of oldest females was very small ( n = 13), which also may have precluded the ability to determine whether body condition declined for the oldest females in that sample (Pitcher et al, 1998 ). However, parturition dates were later for the oldest mothers (parturition dates became earlier from ages 5 to 12 and then became later from ages 12 to 20; Hastings & Jemison, 2016 ; but see Maniscalco & Parker, 2018 ) and later parturition dates were associated with poor body condition in other species (reviewed by Hastings & Jemison, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, sample size of oldest females was very small ( n = 13), which also may have precluded the ability to determine whether body condition declined for the oldest females in that sample (Pitcher et al, 1998 ). However, parturition dates were later for the oldest mothers (parturition dates became earlier from ages 5 to 12 and then became later from ages 12 to 20; Hastings & Jemison, 2016 ; but see Maniscalco & Parker, 2018 ) and later parturition dates were associated with poor body condition in other species (reviewed by Hastings & Jemison, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in times of nutritional stress, marine mammals may forego reproduction or restrict maternal investment. This has most frequently been evidenced in pinnipeds (Maniscalco and Parker, 2017). For example, in a study of Antarctic fur seals (Arctocephalus gazellaon), lower pup weights were found to be associated with a decline in maternal body condition, resulting in a significant percentage of pup mortalities (Lunn and Boyd, 1993).…”
Section: Introductionmentioning
confidence: 96%
“…The timing of the peaks and the actual length of the pupping season at these colonies were not aligned, however, which suggests that the processes influencing the length of the pupping season are not shared between colonies, despite their geographical proximity. Changes that occur in warmer years at the Skomer colony may encourage earlier, more successful weaning and greater survival probability (Bowen et al, 2015;Maniscalco and Parker, 2018;Pomeroy et al, 1999). This may also bring pups born at the Skomer colony in line with those born at the Marloes and Ramsey colonies which may already have a competitive advantage if their earlier weaning is synchronous with greater resource availability.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in phenology -the cyclic timing of life-history events such as breeding -can have consequences from individual to population and community level, affecting connectivity, rates of reproduction and survival, and ecosystem function (Carson et al, 2010;Miller-Rushing et al, 2010;Thackeray et al, 2016). Phenological change has been attributed to a number of drivers, including global climate change, (Chambers et al, 2014;Poloczanska et al, 2016;Thackeray et al, 2016, although see Both, 2005 andBurthe et al, 2012 on the challenge of quantifying this) population density (Votier et al, 2009), resource availability and individual physiological status (Maniscalco and Parker, 2018), and interactions between these processes (Rotella et al, 2016). The ways in which species respond to environmental changes are complex and can vary considerably, and will largely be determined by a species' ecological and physiological characteristics (Poloczanska et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation